2017
DOI: 10.18408/ahuri-8209001
|View full text |Cite
|
Sign up to set email alerts
|

Inquiry into funding and delivery of programs to reduce homelessness

Abstract: AHURI report 279iii AHURI AHURI is a national independent research network with an expert not-for-profit research management company, AHURI Limited, at its centre.AHURI's mission is to deliver high quality research that influences policy development and practice change to improve the housing and urban environments of all Australians.Using high quality, independent evidence and through active, managed engagement, AHURI works to inform the policies and practices of governments and the housing and urban developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Specialist homelessness services in Australia are heavily reliant on government funding. Analysis of the funding profile in the SHS sector found that 84.6 per cent of funding was received through government housing and homelessness agreements, a figure that increased to 94.3 per cent when Indigenous-focused services were considered (Flatau, Zaretzky et al 2017). The heavy reliance on government funding by homelessness services began in the 1980s following the launch of the Australian Government Supported Accommodation Assistance Program and, later, the National Affordable Housing Agreement and associated National Partnership Agreement on Homelessness (Flatau, Wood et al 2015).…”
Section: Resourcing the Shs Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Specialist homelessness services in Australia are heavily reliant on government funding. Analysis of the funding profile in the SHS sector found that 84.6 per cent of funding was received through government housing and homelessness agreements, a figure that increased to 94.3 per cent when Indigenous-focused services were considered (Flatau, Zaretzky et al 2017). The heavy reliance on government funding by homelessness services began in the 1980s following the launch of the Australian Government Supported Accommodation Assistance Program and, later, the National Affordable Housing Agreement and associated National Partnership Agreement on Homelessness (Flatau, Wood et al 2015).…”
Section: Resourcing the Shs Sectormentioning
confidence: 99%
“…Analysis of the funding profile in the SHS sector found that 84.6 per cent of funding was received through government housing and homelessness agreements, a figure that increased to 94.3 per cent when Indigenous-focused services were considered (Flatau, Zaretzky et al 2017). The heavy reliance on government funding by homelessness services began in the 1980s following the launch of the Australian Government Supported Accommodation Assistance Program and, later, the National Affordable Housing Agreement and associated National Partnership Agreement on Homelessness (Flatau, Wood et al 2015). The remaining funding utilised by the SHS sector comes via non-government sources, including non-government organisations (NGOs) that deliver services on the ground and philanthropy (Productivity Commission 2022).…”
Section: Resourcing the Shs Sectormentioning
confidence: 99%
“…Poor housing outcomes and repeat presentations or 'churn' occur within a context of limited exit options from the SHS system. Long-term underinvestment and residualisation of social housing (Flanagan, Levin et al 2020), an escalating shortage of affordable private rental options (Hulse, Reynolds et al 2019), and a funding model based on throughput measures rather than outcomes (Flatau, Zaretzky et al 2017) all impact on what is achieved in the crisis accommodation space.…”
Section: Why Crisis Accommodation?mentioning
confidence: 99%
“…SHSs support those who have become homeless and those who are at imminent risk of homelessness. Importantly, SHSs are funded by diverse sources: state and territory governments, the Australian Government, charitable organisations and other sources, including local governments (Flatau, Zaretzky et al 2017). This has resulted in a highly fragmented system.…”
Section: Executive Summarymentioning
confidence: 99%
“…The research builds explicitly on previous AHURI and other research, as synthesised by Brackertz, Fotheringham et al (2016), and more recent research by AHURI authors (Flatau, Zaretzky et al 2017;Spinney, Habibis et al 2016). We use a systems thinking approach for analysing the homelessness service system and other systems, supported by three interrelated projects that introduce Indigenous methodologies to contribute to a shared overarching conceptual framework.…”
Section: Introductionmentioning
confidence: 99%